2008
DOI: 10.2527/jas.2007-0244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of beef cattle diets containing corn or sorghum distillers grains on beef color, fatty acid profiles, and sensory attributes1,2

Abstract: Strip loins from 236 carcasses from crossbred yearling steers were collected on each of 2 slaughter dates (slaughter 1 or 2) to determine the effects of feeding corn or sorghum distillers grains (DG) on beef color, fatty acid profiles, lipid oxidation, tenderness, and sensory attributes. Dietary treatments consisted of a steam-flaked corn (SFC) diet without (control) or with 15% (DM basis) corn dry or wet DG (CDDG and CWDG) or sorghum dry or wet DG (SDDG and SWDG) and alfalfa hay (R). Additional treatments inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 39 publications
8
52
3
1
Order By: Relevance
“…On the other hand C18:3n-6 showed lower amounts in the DDGS group. Gill et al (2008) reported increased content of n-6 polyunsaturated fatty acids when feeding cattle with DDGS which is in line with our results for C18:2 and opposite to the results of our study for the contents of C18:3n-6. Other studies report increased content of C18:2 in the brisket fat in beef and no change in the content of C18:3n-3 (Dugan et al, 2010).…”
Section: Polyunsaturated Fatty Acidscontrasting
confidence: 40%
“…On the other hand C18:3n-6 showed lower amounts in the DDGS group. Gill et al (2008) reported increased content of n-6 polyunsaturated fatty acids when feeding cattle with DDGS which is in line with our results for C18:2 and opposite to the results of our study for the contents of C18:3n-6. Other studies report increased content of C18:2 in the brisket fat in beef and no change in the content of C18:3n-3 (Dugan et al, 2010).…”
Section: Polyunsaturated Fatty Acidscontrasting
confidence: 40%
“…The LT WBSF and retail display data were analysed with a repeated measures design, with diet, day and their interactions as main effects, slaughter date and pen nested within diet as random effects, and day as the repeated factor. When the random effect of pen nested within diet was not significant, it was removed from carcass traits, meat quality, sensory attributes and FA models and individual animal was used as the experimental unit (Gill et al, 2008). Treatment means were generated and separated using the LSMeans and PDIFF options, respectively.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Bas and Morand-Fehr (2000) showed that the carcass of lambs fed a diet based on maize contained more odd-numbered fatty acids than the lambs given wheat. Gill et al (2008) reported that a diet based on maize or sorghum distiller grains increased steak n-6 fatty acid and linoleic acid concentrations of beef compared with the diet based on a steam-flaked maize. In a previous study with lambs it was found that lipids in different fat depots (endogenous and subcutaneous) of grazing ruminants contained relatively more linolenic acid, with a lower C18:2n-6/ C18:3n-3 ratio, than the concentrate fed animals (Banskalieva et al, 2005).…”
Section: Fatty Acid Composition Of Longissimus Dorsi Musclementioning
confidence: 99%